Analysis of Distribution Network Disruptions Using Fault Tree Analysis: A Case Study of the Bandung Feeder at PT. PLN Bengkalis - Nanang Rizkiawan; Zainal Abidin (Universitas Pendidikan Nasional, 2026)
The electricity distribution network plays an important role in distributing electrical energy from substations to customers. At the Bandung PT. PLN (Persero) ULP Bengkalis feeder, there are still disruptions that cause blackouts and reduce service quality. This study aims to analyze the causes of disruptions using the Fault Tree Analysis (FTA) method to identify the dominant factors and root causes. The methods used include literature studies, observations, interviews, and data collection on disruptions from January 2025 to Desember 2025 This study was motivated by the limitations of previous studies, which generally used Fault Tree Analysis (FTA) only in a descriptive manner without a quantitative approach and did not consider the influence of local factors on power distribution network outages. Therefore, this study aims to develop a semi-quantitative, probability-based FTA approach and to examine the characteristics of outages in the Bengkalis region. The scientific contribution of this study lies in the integration of probabilistic analysis into FTA and the strengthening of risk-based recommendations to improve the reliability of the electrical distribution system. Animals such as birds, squirrels, or other creatures can cause disruptions by coming into contact with or bridging conductors, which can potentially cause short circuits. The high frequency of interactions between electrical networks and their surroundings, combined with a lack of monitoring and protection of the networks, makes these two factors more significant than other causes. When comparing internal and external disruptions, it is evident that external disruptions account for a larger proportion—approximately 59% of total disruptions—while internal disruptions account for about 41%. This confirms that the reliability of the distribution system in the study area is more heavily influenced by external factors than by the technical condition of the equipment itself.